Sustainable production of bioemulsifiers, a critical overview from microorganisms to promising applications - Rubio-Ribeaux, Daylin [UNESP]; da Costa, Rogger Alessandro Mata [UNESP]; Montero-Rodríguez, Dayana [UNESP]; do Amaral Marques, Nathália Sá Alencar [UNESP]; Puerta-Díaz, Mirelys [UNESP]; de Souza Mendonça, Rafael [UNESP]; Franco, Paulo Marcelino [UNESP]; dos Santos, Júlio César [UNESP]; da Silva, Silvio Silvério [UNESP] (Springer Nature, 2023)
Microbial bioemulsifiers are molecules of amphiphilic nature and high molecular weight that are efficient in emulsifying two immiscible phases such as water and oil. These molecules are less effective in reducing surface tension and are synthesized by bacteria, yeast and filamentous fungi. Unlike synthetic emulsifiers, microbial bioemulsifiers have unique advantages such as biocompatibility, non-toxicity, biodegradability, efficiency at low concentrations and high selectivity under different conditions of pH, temperature and salinity. The adoption of microbial bioemulsifiers as alternatives to their synthetic counterparts has been growing in ongoing research. This article analyzes the production of microbial-based emulsifiers, the raw materials and fermentation processes used, as well as the scale-up and commercial applications of some of these biomolecules. The current trend of incorporating natural compounds into industrial formulations indicates that the search for new bioemulsifiers will continue to increase, with emphasis on performance improvement and economically viable processes.
Keywords: Bioreactors; Emulsification index; Lignocellulosic biorefinery; Microbial emulsifiers